Probiotics as modulators of gut-brain axis for cognitive development - Kumar, Akash; Sivamaruthi, Bhagavathi Sundaram; Dey, Swarnima; Kumar, Yogesh; Malviya, Rishabha; Prajapati, Bhupendra G.; Chaiyasut, Chaiyavat (Frontiers in Pharmacology, 2024)
Various microbial communities reside in the gastrointestinal tract of humans and play an important role in immunity, digestion, drug metabolism, intestinal integrity, and protection from pathogens. Recent studies have revealed that the gut microbiota (GM) is involved in communication with the brain, through a bidirectional communication network known as the gut-brain axis. This communication involves humoral, immunological, endocrine, and neural pathways. Gut dysbiosis negatively impacts these communication pathways, leading to neurological complications and cognitive deficits. Both pre-clinical and clinical studies have demonstrated that probiotics can restore healthy GM, reduce intestinal pH, and reduce inflammation and pathogenic microbes in the gut. Additionally, probiotics improve cell-to-cell signaling and increase blood-brain-derived neurotrophic factors. Probiotics emerge as a potential approach for preventing and managing neurological complications and cognitive deficits. Despite these promising findings, the safety concerns and possible risks of probiotic usage must be closely monitored and addressed. This review article provides a brief overview of the role and significance of probiotics in cognitive health.